Liberation Theology of Leftist Islam in the Thought of Hassan Hanafi and its Contextualization - Muhammad Adress Prawira Negara; Neng Hannah (Islamic Thought Review, 2023)
Theology is one of the critical factors for the survival of Muslims. However, with the shift in all aspects included in the lives of Muslims, theology cannot adjust or even solve all the problems occurring in the body of Islam. This research aimed at discussing and studying the theology of Leftist Islam in the thought of Hassan Hanafi to obtain its authenticity. The method used in this study was the historical-philosophical method. This historical method is to describe the history and development of Islamic theology. In comparison, the philosophical method examines a character's thoughts and analyzes the thoughts being studied. The results of this study explained that Leftist Islam is an idea, concept, and new theology initiated by Hassan Hanafi in response to the challenges of the West. In the Leftist Islam, Hassan Hanafi has three crucial elements, namely revitalizing the classical scientific tradition, opposing Western civilization, and analyzing the reality of Muslims.